The impact of the Sarbanes-Oxley act on the cost of going public - Christoph Kaserer; Alfred Mettler; Stefan Obernberger (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2008)
This paper examines the impact of SOX on the total cost and the component cost of going public. First, we document a statistically significant increase in non-underwriting expenses of 0.8 percentage points after the introduction of SOX, which is mostly due to an increase in accounting and legal fees. Because of the fixed-cost character of this component cost, smaller issues show a much greater percentage increase than larger ones. Second, we demonstrate a highly significant reduction in underpricing in the magnitude of about 4 percentage points. This result is size-independent, and in accordance with the view that SOX reduces adverse selection costs. Third, we find that on average the total flotation costs have decreased between 3 and 3.5 percentage points in the post-SOX period. However, for smaller companies the reduction in underpricing does not compensate anymore for the increase in non-underwriting expenses (i.e., accounting and legal fees). Therefore, the positive impact of SOX on the costs of going public decreases with smaller offering sizes.
Keywords: G30; G34; 330; Sarbanes-Oxley; SOX; IPO; Going Public; Adverse Selection; Internes Kontrollsystem; Anlegerschutz; Wertpapieremission; Emissionskurs; Adverse Selection